Pengaruh Kinerja Pemerintah Daerah Dan Karakteristik Pemerintah Daerah Terhadap Voluntary Graphics Disclosure Pada Pemerintah Kabupaten/Kota Di Indonesia Tahun 2017 - Atikah Wulandari; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2019)
The objective of this study is to determine the effect of Local Government Performance, Level of Dependency, Local Government Location and Local Government Wealthy to Voluntay Graphics Disclosure on local government financial report in Indonesia. The sample of this study using the 231 districts/cities in Indonesia period of 2017. Sampling was done by using purposive sampling method. The type of data used is secondary data obtained from local government financial report (LKPD). The analytical method used is multiple linear regression analysis models were performed with SPSS 20.0. Results of regression testing showed that only level of dependency which effect negative and significant to voluntary graphics disclosure, while lokal government performance, local government location and local government wealthy not significantly effect to voluntary graphics disclosure on local government (districts/cities) in Indonesia period of 2017.